The effect of oral contraceptives on bone mass and stress fractures in female runners - Clobb, K. L.; Bachrach, L. K.; Sowers, M.; Nieves, J.; Greendale, G. A.; Kent, K. K.; Brown, B. W.; Pettit, K.; Harper, D. M.; Kelsey, J. L. (Medicine & Science in Sports & Exercise, 2007)
Purpose: To determine the effect of oral contraceptives (OC) on bone mass and stress fracture incidence in young female distance runners.